Different Faces of Parody in Billy Liar - Śliwińska, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
Parody in John Schlesinger’s Billy Liar functions on a number of levels. First of all, it relates to the construction of the main character – his behaviour, way of speaking, facial expression. Billy constantly plays a game with the world in which, according to him, one can live only when pretends someone else. Since its main aim is to imitate and mock others in order to achieve a comical effect, it is easy to state that Billy Fisher is a master of this art. But the character of Schlesinger’s film is expressed not only in the construction of the character (Billy’s aversion to the set patterns of middle-class life and his simultaneous fascination and disdain for mass culture). The director did not hesitate to parody the Angry Young Men cinema too. Thanks to this, he managed to expose the weaknesses of this world-renowned movement in the British cinema. Ironically, in parodistic, artificial behavior of Billy we can see a lot of truth about him, his environment and even the convention used by the director to talk about Billy’s life.